2010
DOI: 10.1177/147323001003800107
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Bone Mineral Density and Clinical Features in Patients with Inflammatory Bowel Disease: A Local Study in Turkish Population

Abstract: This study aimed to compare the bone mineral density (BMD) of patients with ulcerative colitis (UC) and Crohn's disease (CD) in order to determine the possible risk factors for bone loss. A total of 142 patients with UC (n = 88) and CD (n = 54) participated in the study. They were assessed for gender, body mass index (BMI), disease duration and activity, intestinal site of involvement, history of bowel resection, use of steroids, and extraintestinal findings and complications. The BMD was measured by dual-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…[24] The frequency reported in the current study was also higher than the recently reported prevalence in comparably aged Asian patients. [2526] However, our results are similar to recent reports regarding the prevalence of BMD in IBD patients in Egypt and the United States. [2728]…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[24] The frequency reported in the current study was also higher than the recently reported prevalence in comparably aged Asian patients. [2526] However, our results are similar to recent reports regarding the prevalence of BMD in IBD patients in Egypt and the United States. [2728]…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported a trend toward lower BMD in patients with CD when compared with UC patients in both the hip and the lumbar spine,[263134] the hip region alone[24] or the lumbar spine alone. [8] The higher prevalence of bone disease in CD is thought to result from ileal and small intestinal involvement, ileal resection, hepatobiliary complications, and the use of cholestyramine, which can lead to vitamin D deficiency, calcium malabsorption, or malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Poturoglu et al (47) proposed that complications or extra-intestinal involvement were a significant predictor of BMD in both groups. They studied a total of 142 patients with UC (n = 88) and CD (n = 54), and found that steroid use, disease activity, disease localization, disease duration, bowel surgery and gender had no influence on BMD.…”
Section: Complications or Extra-intestinal Involvementmentioning
confidence: 97%